PENGARUH MODEL SMALL-SIDED GAMES TERHADAP KETERAMPILAN SEPAK BOLA ANAK - Rendra Agung P; Dwi Gunadi; Muhammad Syarifudin; Muhammad Ilham Dewanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this research is to see how the small-sided game (SSG) model impacts how elementary school students become more skilled at playing soccer. The research was conducted using a quasi-experimental method and employed a pretest-posttest control group design. This study was conducted at SDN Sayangan Laweyan, Surakarta, and involved 30 students aged between 8 and 12 years. They were divided into an experimental group and a control group, each with 15 students. The experimental group received treatment in the form of small games for six weeks, repeated three times a week, while the control group received normal learning. Dribbling, passing, shooting, tactical decision-making skills tests, observation sheets, and learning motivation questionnaires are the research instruments. To determine the differences before and after the treatment, data analysis was conducted using descriptive statistics and a paired sample t-test. The research results show that the Small-Sided Games model significantly improves students' overall football skills. Dribbling ability increased by 34.5%, passing by 33.0%, and shooting by 35.4%, and decision-making ability increased by 42.5% (p < 0.05). Game-based training also increases students' learning motivation. The results show that small-sided games have the ability to generate active, enjoyable, and student-centered learning. Therefore, it can be used as an alternative to the football learning model in elementary schools.